Adhesive Micropatterns to Study Intermediate Filament Function in Nuclear Positioning. Issue 1 (2nd March 2015) - Dupin, Isabelle; Elric, Julien; Etienne‐Manneville, Sandrine
Abstract: The nucleus is generally found near the cell center; however its position can vary in response to extracellular or intracellular signals, leading to a polarized intracellular organization. Nuclear movement is mediated by the cytoskeleton and its associated motors. While the role of actin and microtubule cytoskeletons in nuclear positioning has been assessed in various systems, the contribution of intermediate filaments is less established due in part to the lack of tools to study intermediate filament functions. The methods described here use micropatterned substrates to impose reproducible cell shape and nucleus position. Intermediate filament organization can be perturbed using gene downregulation or upregulation; intermediate filaments can also be visualized using fluorescent intermediate filament proteins. This protocol is valuable for characterizing the role of intermediate filaments in a variety of live or fixed adherent cells. © 2015 by John Wiley & Sons, Inc.